Method of physical improvement of higher education students by means of functional training in the aspect of health-preservation - Otravenko, Olena; Shkola, Olena; Zhamardiy, Valeriy; Pavliuk, Olena; Radchenko, Alina; Donchenko, Viktoriia; Myronenko, Svitlana (My University, 2024)
Aim: To justify and experimentally verify the modern method of physical improvement of higher education students by means of functional training, taking into account the individual capabilities of student age in the aspect of health-preservation. Materials and Methods: 264 students of the 1st-2nd years of the specialties: «Physical therapy, occupational therapy», «Technologies of medical diagnosis and treatment», specialty «Secondary education. Physical culture» and «Physical culture and sport. Sport» took part in the study. They attended physical education classes and extracurricular functional training classes during 2020-2022 in three stages: theoretical and diagnostic stage; analytical and research stage; experimental and generalizing stage. Students were from the Educational and Scientific Institute of Physical Education and Sports of the State Institution «Luhansk National University named after Taras Shevchenko», the Communal Institution «Kharkiv Humanitarian and Pedagogical Academy» of the Kharkiv Regional Council. Research methods: theoretical, empirical, methods of statistical data processing. Results: The survey of the tested contingent showed that 60% of respondents want to increase muscle mass, increase strength – 30%, correct the figure – 10%. Among the forms of classes, 46% students consider independent classes to be the best, physical education classes – 40%, personal and group classes – 14%. Conclusions: An experimental method of physical improvement of students of higher education institutions using functional training exercises has been developed. A feature of the developed methodology is the individualization and integral combination of traditional teaching methods with innovative ones with gradual complication of the content of classes.
Method of physical improvement of higher education students by means of functional training in the aspect of health-preservation / Olena Otravenko, Olena Shkola, Valeriy Zhamardiy, Olena Pavliuk, Alina Radchenko, Viktoriia Donchenko, Svitlana Myronenko // Acta Balneologica: Journal of the polish balneology and physical medicine association. Aluna Publishing, 2024. – Vol. LXVI ISSUE 1(179), JANUARY-FEBRUARY 2024. – 66(1). – Р. 40-48
Keywords: technique, physical improvement, students of higher education, quality of training, means of functional training, health-preservation